ANALISIS PENERAPAN COST LEADERSHIP STRATEGY DI CV. MEKAR MANDIRI BANDUNG - Susanto, Valencia; Shelvi (Jurnal Administrasi Bisnis, 2023)
The development of increasingly fierce competition in the printing industry has forced printing service businesses to lower their selling prices and look for cheap paper distributors. Growth and high market demand create new business opportunities for printing service businesses to increase customers and sales. This research is descriptive with the type of qualitative research. The research method used is descriptive analysis with a case study approach. The collection technique was carried out by interviews and observation. The data analysis techniques used in this study are external environmental analysis (PESTEL and the 5 Forces Model), internal environmental analysis (SWOT) and analysis of the Company's Cost Leadership strategy. Based on the research results, it can be concluded that the implementation of the Cost Leadership strategy by CV. Mekar Mandiri is good. The company has reduced costs to increase the company's competitiveness. The company is able to reduce operational costs and get low prices from suppliers so that the company can sell products to buyers at low prices. CV. Mekar Mandiri has chosen the right strategy, namely the Cost Leadership strategy. CV.Mekar Mandiri provides recommendations for what companies can do to make the company better, namely setting discounts that are categorized more clearly.